Current aspects of the principal of protecting employees - Jovanović Predrag (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2011)
The principal of protecting employees is traditionally present in labor law. Particular categories of employees, also traditionally, enjoy special protection (young people, women, the disabled). However, the issue of protection of moral integrity of the employees has only recently been addressed. That makes the general principle of the protection of employees in labor relations very current, and it is from that perspective that this paper points out to certain standards of protection of employees in light of international, European and domestic law.